Seasonal dynamics of wintering waterbirds in two shallow lakes along Yangtze River in Anhui Province - CHEN, Jin-Yun; ZHOU, Li-Zhi; ZHOU, Bo; XU, Ren-Xin; ZHU, Wen-Zhong; XU, Wen-Bin (Kunming Institute of Zoology, Chinese Academy of Sciences, 2012)
The shallow lake wetlands in the middle and lower Yangtze River floodplain are important wintering and stopover habitats for migratory waterbirds on the East Asia-Australia Flyway. With increasing fishery practices in recent years, however, the wetlands have deteriorated significantly and now threaten wintering waterbirds. To gain insight into the influence of deteriorating wetlands on waterbirds, we conducted a survey of wintering waterbird species, population size, and distribution across 11 belt transects in Caizi Lake and Shengjin Lake, two shallow lakes along the Yangtze River in Anhui Province from November 2007-April 2008 and from November 2008-April 2009, respectively. The impacts of different fishery patterns on the distribution of waterbirds were also analyzed. A total of 43 waterbirds species belong to 7 orders of 12 families were counted during the surveys, of which 38 were found in Caizi Lake with a density of 8.2 ind./hm2, and 42 in Shengjin Lake with a density of 3.5 ind./hm2. Geese ( Anser cygnoides ), bean geese ( Anser fabalis ), tundra swan ( Cygnus columbianus ), and dunlin ( Calidris alpina ) were the dominant species in the two shallow lakes. Species number and individual assemble reached maximum at the end of December and in early January of the following year, without coincidence of the largest flock for different ecological groups. Based on waterbird diversity across the 11 belt transects and the fishery patterns, habitats could be divided into three groups. Gruiformes, Anseriformes and Charadriiformes had relatively higher densities in the natural fishery zones and lower densities in the cage fishery zones; whereas, the density of Ardeidae showed little change across all lake zones. It is important to develop sustainable fishery patterns in shallow lakes along the middle and lower Yangtze River floodplain to better protect resources of wintering waterbirds.